Contraband detection thechnological complex with ion linac - Gavrish, Yu.N; Svistunov, Yu.A.; Sidorov, A.V.; Fialkovsky, A.M. (Вопросы атомной науки и техники, 2004)
The contraband detection technological complex (CDTC) to detect explosives, fission materials, and vegetable drugs is proposed. Our approach employs the pulsed neutron source. The CDTC employs the rf linac to provide a beam of deuterons of 1 or 3.5 MeV, which impinge upon a target giving birth pulsed neutron flow. Explosives are
identified by the matrix detection system with gamma registration under interaction of neutron on N, O, C nuclei. Experimental verification of main principles of matrix detection system is presented. Дано опис комплексу виявлення вибухових, що поділяються і наркотичних речовин рослинного походження. Джерелом зондувального нейтронного випромінювання є лінійний малогабаритний над частотний прискорювач іонів водню. Представлено результати іспиту системи детектування й обробки інформації гамма-випромінювання, створеного при взаємодії нейтронного випромінювання з характерними елементами N, O, C, що входять до складу шуканих матеріалів. Дано описание комплекса обнаружения взрывчатых, делящихся и наркотических веществ растительного происхождения. Источником зондирующего нейтронного излучения является линейный малогабаритный высокочастотный ускоритель ионов водорода. Представлены результаты испытания системы детектирования и обработки информации гамма-излучения, образуемого при взаимодействии нейтронного излучения с характерными элементами N, O, C, входящими в состав искомых материалов.